Du suivi GPS des individus à une approche chronotopique - Luc Gwiazdzinski; Olivier Klein (Netcom)
This communication deals with an assessment of the GPS use for analysing complex trips of hypermodern individuals. Based on research conducted since a dozen years in France and Grand Duchy of Luxembourg, it shows the importance of these systems in the analysis of mobility and possible contributions for public transport policies. From a focus on cartographic representations produced as tools for analysis and dialogue with the public and the policy makers, it sets out some pointers for the future.